The Problem Is They See Us As A Whole : Explaining Gender and Ethnicity-based Inequalities Among the Roma in Serbia - World Bank (World Bank, Washington, DC, 2019)
The objective of this report is to analyze the gender norms of Roma and non-Roma men and women in marginalized neighborhoods of Serbia, and assess the impact of these norms on schooling, work, and household decision-making.This report aims to generate and promote the use of evidence on living conditions and human development outcomes among marginalized Roma communities of the Western Balkans and their neighboring non-Roma counterparts and provide evidence-based recommendations for policy and programming. The primary universe for the Regional Roma Survey is: (i) all households in Roma settlements or areas of compact Roma population; and (ii) non-Roma communities living in close proximity to marginalized Roma. The results of the RRS 2017 show that marginalized Roma in Serbia, much like the rest of the Western Balkans, do not have the endowments and assets they need nor the ability to use the assets they have efficiently and intensively to generate economic gains and climb up the socioeconomic ladder. This qualitative report makes three main contributions. First, the gaps between Roma and non-Roma in schools, work places, and household decision making revealed by the RRS 2017 are placed within a structural marginalization or social exclusion framework.Second and most critically, we find a broad range of diversity within the Roma population in Serbia. Unfortunately, Roma are often homogenized in both academic and policy literature.The findings of this report move beyond flattening histories and attributing norms and beliefs to a static and singular “identity” and allegedly common “culture.”Third, the authors find that social norms fluctuate and shift as the wider context shifts – that within Serbia, there is significant variation among the Roma living in three different contexts (urban, post-industrial and agricultural). Using this perspective, they illuminate the mechanisms of change with respect to gender and ethnicity that remain invisible in the RRS 2017 but result in the diverging impacts captured by it.The paper is structured as follows. Section two reviews the literature and current knowledge on marginalized Roma and social exclusion in Serbia, and notes the gaps in the literature. Section three gives a description of the methodology of the study and the sample used for analysis. Section four presents key findings from the study on gender norms in work, schooling, and household decision making. Section five, six, and seven present the three case studies and a detailed overview of the location- and context-specific barriers for Roma versus non-Roma households demonstrating how these three locations – one urban, one post-industrial and one agricultural – offer important insights into the variation in constraints and forms of exclusion of the Roma. Section eight draws on the findings to provide concrete recommendations for policy interventions and concludes.